Is There an Association Between Bone Microarchitecture and Fracture in Patients who were Treated for High-grade Osteosarcoma? A Controlled Study at Long-term Follow-up Using High-resolution Peripheral Quantitative CT. Issue 11 (2nd November 2021) - Holzer, Gerold; Hobusch, Gerhard; Hansen, Stinus; Fischer, Lukas; Patsch, Janina M.
Abstract: Background: Neoadjuvant chemotherapy in patients with primary osteosarcoma improves survival rates, but it also causes side effects in various organs including bone. Low bone mineral density (BMD) can occur owing partly to chemotherapy or limited mobility. This can cause a higher risk of fractures compared with those who do not receive such treatment. Changes in BMD alone cannot explain the propensity of fractures. Studying microarchitectural changes of bone might help to understand the effect. Questions/purposes: (1) Do patients who were treated for osteosarcoma (more than 20 years previously) have low BMD? (2) Do these patients experience more fractures than controls who do not have osteosarcoma? (3) What differences in bone microarchitecture are present between patients treated for high-grade osteosarcoma and individuals who have never had osteosarcoma? Methods: We contacted 48 patients who were treated for osteosarcoma and who participated in an earlier study. These patients underwent multimodal treatment including chemotherapy more than 20 years ago. Of the original patient group, 60% (29 of 48) were missing, leaving 40% (19 of 48) available for inclusion in this study; all 19 agreed to participate. There were nine men and 10 women with a mean age of 46 ± 4 years and a mean time from surgery to examination of 28 ± 3 years. BMD was measured by dual-energy x-ray absorptiometry, and any fracture history was assessed using a questionnaire. Additionally, high-resolution peripheral quantitative CT was performed to compare the groups in terms of microarchitectural changes, such as cortical and trabecular area, cortical and trabecular thickness, cortical porosity, and endocortical perimeter. Participants in the control group were selected from a cohort consisting of a population-based random sample of 499 healthy adult women and men. Osteoporosis or low BMD was not an exclusion criterion for entering this study; however, the patients in the control group were selected based on a normal BMD (that is, T score > -1.0 at both the spine and hip). Also, the participants were matched based on age and sex. Differences between patients and controls were assessed using the Wilcoxon rank sum test for continuous variables and a chi-square test for categorical variables. A multiple regression analysis was performed. Model assumptions were checked using histograms and quantile-quantile plots of residuals. Results: Twelve of 19 patients who were treated for osteosarcoma had either osteopenia (eight patients) or osteoporosis (four patients). More patients with osteosarcoma reported sustaining fractures (11 of 19 patients) than did control patients (2 of 19 controls; p < 0.001). Among all microarchitectural parameters, only the endocortical perimeter was increased in patients compared with the control group (75 ± 15 mm versus 62 ± 18 mm; p = 0.04); we found no differences between the groups in terms of cortical and trabecular area, cortical and trabecular thickness, or cortical porosity. Conclusion: Although patients who were treated for osteosarcoma had osteopenic or osteoporotic BMD and a higher proportion of patients experienced fractures than did patients in the control group, we could not confirm differences in microarchitectural parameters using high-resolution peripheral quantitative CT. Therefore, it seems that bone geometry and microstructural parameters are not likely the cause of the increased proportion of fractures observed in our patients who were treated for osteosarcoma. Until we learn more about the bone changes associated with chemotherapy in patients with osteosarcoma, we recommend that patients undergo regular BMD testing, and we recommend that physicians consider osteoporosis treatment in patients with low BMD. These data might provide the impetus for future multicenter prospective studies examining the association between chemotherapy and bone microarchitecture. Level of Evidence: Level III, therapeutic study.